2020
DOI: 10.1002/imhj.21841
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving representations in war conditions: Associations with maternal trauma, mental health, and mother–infant interaction

Abstract: Risk features in mothers' caregiving representations remain understudied in dangerous environments where infants most urgently need protective parenting. This pilot study examines the feasibility of a novel coding system for the Parent Development Interview (PDI) interview (ARR, Assessment of Representational Risk) in assessing 50 war-exposed Palestinian mothers' caregiving representations. First, we explored the content and structure of risks in the representations. Second, we examined associations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…It is also likely that different factor structures are evident in different samples. Indeed, this has been shown to be the case in a recent application of the ARR coding in a sample of war‐exposed Palestinian mothers (Isosävi et al., 2020). Given the low internal consistency of some subscales and the likelihood of very different factor structures for different parenting populations, we recommend that the ARR total score be taken as the most robust indicator of risk.…”
Section: Discussionmentioning
confidence: 82%
“…It is also likely that different factor structures are evident in different samples. Indeed, this has been shown to be the case in a recent application of the ARR coding in a sample of war‐exposed Palestinian mothers (Isosävi et al., 2020). Given the low internal consistency of some subscales and the likelihood of very different factor structures for different parenting populations, we recommend that the ARR total score be taken as the most robust indicator of risk.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, Negrao et al (2016) found that preoccupied attachment (assessed with the Adult Attachment Interview) was associated with lower observed EA, studied in 1-4-year-old children and their mothers. In contrast to the above, but also implemented in the Palestinian context, Isosävi et al (2020) did not find a link between the mother's experience of traumatic war events and EA-SR, but mothers with postnatal post-traumatic stress disorder (PTSD) reported lower EA-SR, concurrently assessed at 1 year of age. It is also important to mention that the authors indicated possible unreliable results from traumatized mothers, mentioning that "self-reported interaction quality is a type of maternal representation of the relationship and hence subject to distortions" (p. 258).…”
Section: Resultsmentioning
confidence: 60%
“…In clinical samples, distorted representations are often associated with interpersonal trauma, stress, and anxiety (Isosävi et al., 2020; Newman‐Morris, Simpson, et al., 2020; Sleed et al., 2021). Our sample is drawn from a diverse, urban community and the most common risk factors among participants was poverty and exposure to violence.…”
Section: Discussionmentioning
confidence: 99%